When gifted kids don't have all the answers : how to meet their social and emotional needs - Galbraith, Judy, 1954-; Delisle, James R., 1953- (Free Spirit Publishing, 2015)
"Gifted kids are so much more than test scores and grades. Still, it's sometimes difficult to see past the potential to the child who may be anxious, lonely, confused, or unsure of what the future might bring. This book, now fully revised with updated information and new survey quotes, offers practical suggestions for addressing the social and emotional needs of gifted students. The authors present ways to advocate for gifted education; help gifted underachievers, perfectionists, and twice-exceptional students; and provide all gifted kids with a safe, supportive learning environment. Complete with engaging stories, strategies, activities, and resources, this book is for anyone committed to helping gifted students thrive. Includes online digital content"--Resumé vydavatele